Non-equimolar-ratio high-entropy thermoelectric ceramic and preparation method thereof

By designing A-position non-equimolar ratio high-entropy perovskite thermoelectric ceramics (Ca1/3Sr1/3Ba1/3)1-xLaxTiO3, the problem of low thermoelectric performance of existing perovskite structural thermoelectric materials is solved, high conductivity, low thermal conductivity and high Seebeck coefficient are achieved, and the thermoelectric conversion efficiency is improved.

CN119528564AActive Publication Date: 2025-02-28NORTHWESTERN POLYTECHNICAL UNIV

Patent Information

Application Number
CN202410649085.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-05-23
Publication Date
2025-02-28
Estimated Expiration
2044-05-23

AI Technical Summary

Technical Problem

The existing perovskite structure SrTiO3-based thermoelectric materials have low thermoelectric properties and high thermal conductivity, which limits their further development in the field of thermoelectric materials.

Method used

A non-equimolar ratio high-entropy perovskite thermoelectric ceramic of A position is designed, with the chemical formula of (Ca1/3Sr1/3Ba1/3)1-xLaxTiO3 (x=0.1~0.4). Through specific raw material ratio and preparation processes, including ball milling, prefiring, discharge plasma sintering and reduction annealing, a high-entropy ceramic with excellent thermoelectric properties is prepared.

Benefits of technology

High conductivity, high Seebeck coefficient and low thermal conductivity are achieved, the thermoelectric conversion efficiency is improved, and an effective path to prepare high-temperature thermoelectric materials is provided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119528564A_ABST
    Figure CN119528564A_ABST
Patent Text Reader

Abstract

The invention relates to a non-equimolar-ratio high-entropy thermoelectric ceramic and a preparation method thereof. The chemical formula of the non-equimolar-ratio high-entropy thermoelectric ceramic is (Ca1 / 3Sr1 / 3Ba1 / 3) 1-xLaxTiO3 (x = 0.1-0.4). Through presintering, spark plasma sintering and reduction annealing processes, a single-phase perovskite structure composed of phases of the A-site high-entropy perovskite thermoelectric ceramic is obtained, equiaxed crystal grains are arranged in the ceramic, and the morphology of the equiaxed crystal grains is matched with that of cubic perovskite structure crystal grains. Elements Ca, Sr, Ba, La, Ti and O in the ceramic are uniformly distributed in the ceramic, and no agglomeration phenomenon exists. The A-bit non-equimolar-ratio high-entropy perovskite thermoelectric ceramic (Ca1 / 3Sr1 / 3Ba1 / 3) 1-xLaxTiO3 obtained by the invention has low thermal conductivity, high conductivity and Seebeck coefficient, further shows a high thermoelectric ZT figure of merit, is simple to operate and short in time period, and provides an effective path for preparing high-temperature thermoelectric materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of high entropy ceramics, and in particular to an A-site non-equimolar high entropy perovskite thermoelectric ceramic (Ca 1 / 3Sr 1 / 3 Ba 1 / 3 ) 1-x La x TiO3 and its preparation method. Background Art

[0002] Thermoelectric materials are functional materials that can realize the mutual conversion of heat energy and electrical energy. They have been widely used in deep space exploration, communication equipment and other fields. In order to achieve higher thermoelectric conversion efficiency, thermoelectric materials need to have high electrical conductivity, high Seebeck coefficient and low thermal conductivity. Thermoelectric ceramics have the advantages of good high-temperature stability, simple preparation process, wide variety, low cost and environmental friendliness, and have attracted widespread attention from scholars. Cubic perovskite phase SrTiO3 has the advantages of high melting point (2080℃), large effective carrier mass, moderate bandgap width (3.2eV) and other advantages, making it one of the most promising n-type thermoelectric ceramic materials. However, due to its high thermal conductivity (12W / m / K at room temperature), its further development is hindered.

[0003] In 2004, the concept of "high entropy alloys" (HEAs) was proposed. Cantor et al. prepared the first single-phase multi-component alloy with stable configurational entropy. Since then, high entropy engineering has been widely studied in the field of alloys. Until 2015, entropy-stabilized ceramics (Mg 0.2 Zn 0.2 Co 0.2 Cu 0.2 Zn 0.2 )O was reported, the concept of high entropy entered the field of ceramics. Drawing on and inheriting high entropy alloys, high entropy ceramics are single-phase ceramics formed by four or more elements in equiatomic ratios or nearly equiatomic ratios. Due to the lattice distortion effect of the high entropy ceramic structure and the hysteresis diffusion effect in kinetics, it can achieve broadband scattering of phonons, thereby reducing the thermal conductivity of the material. Therefore, high entropy engineering has become an important means to optimize the performance of thermoelectric materials. At present, the high entropy design of perovskite structure thermoelectric materials is still mainly equimolar design, and research on non-equimolar design is very rare.

[0004] In the invention with the publication number CN 109607615 A, a B-site high entropy perovskite ceramic and a preparation method thereof are proposed. The invention discloses a B-site high entropy perovskite ceramic of Ba(Zr 1 / 6 Sn 1 / 6 Ti 1 / 6 Hf 1 / 6 Nb 1 / 6 Ga1 / 6 )O3, high entropy perovskite ceramics were prepared by solid phase reaction method, and the phase composition and microstructure of the material were characterized, but the material composition was an equimolar high entropy ceramic material, and the functionality of the material was not described.

[0005] The invention with the publication number CN 117776692 A discloses a high entropy perovskite type high temperature negative temperature coefficient thermistor ceramic, a preparation method and an application. The chemical formula of the disclosed high entropy perovskite type thermistor ceramic is (La 0.2 Nd 0.2 Sm 0.2 Eu 0.2 A 0.2 )CrO3 (A is one of Pr, Tb, Dy, Ho, Er, Yb, Lu, and Y). However, the material composition is an equimolar high-entropy ceramic material, and the high-entropy perovskite ceramic material does not have thermoelectric properties and cannot be applied to the field of thermoelectric materials.

[0006] The invention with the publication number of CN 114133215 A discloses an A-site high entropy perovskite ReMnO3 thermoelectric ceramic and a preparation method thereof. The chemical composition formula of the proposed A-site high entropy perovskite thermoelectric ceramic is (Ca 0.2 Sr 0.2 Ba 0.2 Y 0.2 Nd 0.2 )MnO3 and (Ca 0.2 Sr 0.2 Ba 0.2 Y 0.2 Ho 0.2 )MnO3. The material composition is an equimolar high entropy ceramic material, but the invention does not focus on the non-equimolar high entropy design of the thermoelectric material of the system.

[0007] In DOI:10.1016 / j.jeurceramsoc.2024.02.022, Yibing Zhu et al. published "Ultra-low thermal conductivity in a perovskite oxide thermoelectric throughentropy engineering". In this paper, high entropy perovskite ceramics (Ca 0.33 Sr 0.33 Ba 0.33 )(Ti 0.5- x Zr 0.5-x Nb x)O3, and its thermoelectric properties were studied. The material was prepared by the traditional solid phase method without using SPS sintering and reduction annealing process.

[0008] At present, it has not been seen that CaCO3, SrCO3, BaCO3, La2O3, and TiO2 are used to prepare high-entropy thermoelectric ceramics with non-equimolar ratio of perovskite structure. The present invention designs a high-entropy thermoelectric ceramic with non-equimolar ratio of A position, and its chemical formula is (Ca 1 / 3Sr 1 / 3 Ba 1 / 3 ) 1-x La x TiO3 (x=0.1-0.4) has high electrical conductivity, high Seebeck coefficient and low thermal conductivity. There are no reports on this kind of A-site non-equimolar high-entropy perovskite thermoelectric ceramics. Summary of the invention

[0009] In order to overcome the problem of low thermoelectric performance of current perovskite structure SrTiO3-based thermoelectric materials, the present invention proposes a non-equimolar ratio high entropy thermoelectric ceramic and a preparation method thereof.

[0010] The chemical formula of the non-equimolar ratio high entropy perovskite ceramic thermoelectric ceramic is (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 1-x La x TiO3, (x=0.1~0.4).

[0011] The synthesis of (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 1-x La x The raw materials of TiO3 are CaCO3, SrCO3, BaCO3, La2O3 and TiO2. The particle sizes are all micron-level and the purity is analytical grade.

[0012] Preparation (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 1-x La x The specific process of TiO3 is:

[0013] Step 1, Ingredients:

[0014] According to the stoichiometric ratio of each component in the chemical composition formula of the high entropy perovskite ceramic, each initial raw material is weighed.

[0015] Step 2, ball milling:

[0016] The raw material powder weighed in step 1 is added to a polytetrafluoroethylene ball mill with anhydrous ethanol as the ball milling medium and zirconium oxide balls as the ball milling beads, and ball milled at a speed of 250-350r / min for 12 to 24 hours. The weight ratio of the ball milling medium to the raw material powder is 1:1, and the weight ratio of the ball milling beads to the raw material powder is 2:1. The ball-milled slurry is placed in an oven for drying at a drying temperature of 50 to 60°C for 3 to 12 hours; grind to obtain a powder.

[0017] Step 3, pre-burning:

[0018] The powder obtained in step 2 is placed in a closed crucible, heated to 1150-1250°C at a heating rate of 2-5°C in a high-temperature muffle furnace, kept at this temperature for 2-4 hours, cooled to 500°C at a cooling rate of 2-5°C, and then cooled in the furnace to obtain a high entropy ceramic powder.

[0019] Step 4, secondary ball milling:

[0020] The high entropy ceramic powder obtained in step 3 is subjected to secondary ball milling, and the ball milling process is the same as the first ball milling to obtain (Ca) with an average particle size of 2.7 to 3.4 μm. 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 1-x La x TiO3 high entropy ceramic powder.

[0021] Step 5, spark plasma sintering:

[0022] The powder after secondary ball milling obtained in step 4 is loaded into a graphite mold and sintered by spark plasma sintering technology. The sintering environment is vacuum, the axial pressure applied by the pressure head to the graphite mold is 30-40 MPa, the heating rate is 100°C / min, and the temperature is kept at 1150-1250°C for 3-7 minutes, then cooled to 600°C at a rate of 100°C / min and cooled with the furnace to obtain A-site non-equimolar ratio high entropy perovskite dense ceramics.

[0023] Step 6, reduction annealing:

[0024] The ceramic obtained in step 5 is placed in an alumina crucible with graphite powder added, and the crucible is placed in a tube furnace, argon is introduced, and the temperature is raised to 1200-1400°C at a rate of 2-5°C / min and kept for 4-8h. 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 1-x La x TiO3.

[0025] The purpose of the present invention is to provide an A-site high entropy perovskite thermoelectric ceramic (Ca 1 / 3Sr 1 / 3 Ba 1 / 3 ) 1-x La x TiO3 material and preparation method thereof. The method has the advantages of simple operation and short time cycle. The prepared high entropy ceramic has the advantages of high electrical conductivity, high Seebeck coefficient and low thermal conductivity, and thus has excellent thermoelectric conversion efficiency, providing an effective path for the preparation of high-temperature thermoelectric materials.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] A pure phase A-site non-equimolar ratio high entropy perovskite thermoelectric ceramic was obtained. The chemical formula of the material is (Ca 1 / 3 Sr 1 / 3Ba 1 / 3 ) 1-x La x TiO3 (x = 0.1 ~ 0.4). Figure 1 It is shown that the phase composition of the A-site high entropy perovskite thermoelectric ceramic obtained by the process of the present invention is a single-phase perovskite structure without the presence of a second phase. Figure 2 ~Attached Figure 5 The present invention shows that the A non-equimolar ratio high entropy perovskite ceramic (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 1-x La x The scanning electron microscope photo of the microstructure of TiO3 ceramics shows that the ceramics have equiaxed grains inside, which is consistent with the grain morphology of the cubic perovskite structure. Figure 2 ~Attached Figure 5 It shows that the elements Ca, Sr, Ba, La, Ti, and O in the ceramic are evenly distributed inside the ceramic without agglomeration. Figure 6 ~Attached Fig. 9 The A-site non-equimolar ratio high entropy perovskite thermoelectric ceramic (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 1-x La x The thermoelectric performance of TiO3 varies with temperature. The A-site non-equimolar ratio high entropy perovskite thermoelectric ceramic (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 1- x La xTiO3 has low thermal conductivity, high electrical conductivity and Seebeck coefficient, thus showing high thermoelectric ZT figure of merit. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The present invention is a high entropy perovskite thermoelectric ceramic (CaCO3, SrCO3, BaCO3, La2O3, TiO2) made of A-site non-equimolar ratio 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 1-x La x X-ray diffraction pattern of TiO3.

[0029] Figure 2 The present invention is a high entropy perovskite thermoelectric ceramic (CaCO3, SrCO3, BaCO3, La2O3, TiO2) made of A-site non-equimolar ratio 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.9 La 0.1 Microstructure morphology of TiO3 and distribution of elements Ca, Sr, Ba, La, and Ti in ceramics; Figure 2 a is the A-site non-equimolar ratio high entropy perovskite thermoelectric ceramic (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.9 La 0.1 Microstructure morphology of TiO3; Figure 2 b is the non-equimolar ratio high entropy perovskite thermoelectric ceramic (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.9 La 0.1 Distribution diagram of Ca element in TiO3; Figure 2 c is a non-equimolar ratio high entropy perovskite thermoelectric ceramic (Ca 1 / 3 Sr 1 / 3Ba 1 / 3 ) 0.9 La 0.1 Sr element distribution diagram in TiO3; Figure 2 d is the non-equimolar ratio of high entropy perovskite thermoelectric ceramics (Ca 1 / 3 Sr 1 / 3Ba 1 / 3 ) 0.9 La 0.1 Distribution diagram of Ba element in TiO3; Figure 2 e is a non-equimolar ratio high entropy perovskite thermoelectric ceramic (Ca 1 / 3 Sr 1 / 3Ba 1 / 3) 0.9 La 0.1 Distribution diagram of La element in TiO3; Figure 2 f is the A-site non-equimolar ratio high entropy perovskite thermoelectric ceramic (Ca 1 / 3 Sr 1 / 3Ba 1 / 3 ) 0.9 La 0.1 Distribution diagram of Ti element in TiO3.

[0030] Figure 3 The present invention is a high entropy perovskite thermoelectric ceramic (CaCO3, SrCO3, BaCO3, La2O3, TiO2) made of A-site non-equimolar ratio 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.81 La 0.19 Microstructure morphology of TiO3 and distribution of elements Ca, Sr, Ba, La, and Ti in ceramics. Figure 3 a is the A-site non-equimolar ratio high entropy perovskite thermoelectric ceramic (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.81 La 0.19 Microstructure morphology of TiO3; Figure 3 b is the non-equimolar ratio high entropy perovskite thermoelectric ceramic (Ca 1 / 3 Sr 1 / 3Ba 1 / 3 ) 0.81 La 0.19 Distribution diagram of Ca element in TiO3; Figure 3 c is a non-equimolar ratio high entropy perovskite thermoelectric ceramic (Ca 1 / 3Sr 1 / 3 Ba 1 / 3 ) 0.81 La 0.19 Distribution diagram of Sr element in TiO3; Figure 3 d is the non-equimolar ratio of high entropy perovskite thermoelectric ceramics (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.81 La 0.19 Distribution diagram of Ba element in TiO3; Figure 3 e is a non-equimolar ratio high entropy perovskite thermoelectric ceramic (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.81 La 0.19 Distribution diagram of La element in TiO3; Figure 3 f is the A-site non-equimolar ratio high entropy perovskite thermoelectric ceramic (Ca1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.81 La 0.19 Distribution diagram of Ti element in TiO3.

[0031] Figure 4 The present invention is a high entropy perovskite thermoelectric ceramic (CaCO3, SrCO3, BaCO3, La2O3, TiO2) made of A-site non-equimolar ratio 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.78 La 0.22 Microstructure morphology of TiO3 and distribution of elements Ca, Sr, Ba, La, and Ti in ceramics. Figure 4 a is the A-site non-equimolar ratio high entropy perovskite thermoelectric ceramic (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.78 La 0.22 Microstructure morphology of TiO3; Figure 4 b is the non-equimolar ratio high entropy perovskite thermoelectric ceramic (Ca 1 / 3 Sr 1 / 3Ba 1 / 3 ) 0.78 La 0.22 Distribution diagram of Ca element in TiO3; Figure 4 c is a non-equimolar ratio high entropy perovskite thermoelectric ceramic (Ca 1 / 3Sr 1 / 3 Ba 1 / 3 ) 0.78 La 0.22 Sr element distribution diagram in TiO3; Figure 4 d is the non-equimolar ratio of high entropy perovskite thermoelectric ceramics (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.78 La 0.22 Distribution diagram of Ba element in TiO3; Figure 4 e is a non-equimolar ratio high entropy perovskite thermoelectric ceramic (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.78 La 0.22 Distribution diagram of La element in TiO3; Figure 4 f is the A-site non-equimolar ratio high entropy perovskite thermoelectric ceramic (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.78 La 0.22Distribution diagram of Ti element in TiO3.

[0032] Figure 5 The present invention is a high entropy perovskite ceramic (CaCO3, SrCO3, BaCO3, La2O3, TiO2) made of A-site non-equimolar ratio 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.6 La 0.4 Microstructure morphology of TiO3 and distribution of elements Ca, Sr, Ba, La, and Ti in ceramics. Figure 5 a is the A-site non-equimolar ratio high entropy perovskite thermoelectric ceramic (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.6 La 0.4 Microstructure morphology of TiO3; Figure 5 b is the non-equimolar ratio high entropy perovskite thermoelectric ceramic (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.6 La 0.4 Distribution diagram of Ca element in TiO3; Figure 5 c is a non-equimolar ratio high entropy perovskite thermoelectric ceramic (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.6 La 0.4 Distribution diagram of Sr element in TiO3; Figure 5 d is the non-equimolar ratio of high entropy perovskite thermoelectric ceramics (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.6 La 0.4 Distribution diagram of Ba element in TiO3; Figure 5 e is a non-equimolar ratio high entropy perovskite thermoelectric ceramic (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.6 La 0.4 Distribution diagram of La element in TiO3; Figure 5 f is the A-site non-equimolar ratio high entropy perovskite thermoelectric ceramic (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.6 La 0.4 Distribution diagram of Ti element in TiO3.

[0033] Figure 6The present invention is a high entropy perovskite thermoelectric ceramic (CaCO3, SrCO3, BaCO3, La2O3, TiO2) made of A-site non-equimolar ratio 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.9 La 0.1 TiO3, (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.81 La 0.19 TiO3, (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.78 La 0.22 TiO3, (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.6 La 0.4 Thermal conductivity of TiO3 versus temperature.

[0034] Figure 7 The present invention is a high entropy perovskite thermoelectric ceramic (CaCO3, SrCO3, BaCO3, La2O3, TiO2) made of A-site non-equimolar ratio 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.9 La 0.1 TiO3, (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.81 La 0.19 TiO3, (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.78 La 0.22 TiO3, (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.6 La 0.4 The conductivity of TiO3 changes with temperature.

[0035] Figure 8 The present invention is a high entropy perovskite thermoelectric ceramic (CaCO3, SrCO3, BaCO3, La2O3, TiO2) made of A-site non-equimolar ratio 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.9 La 0.1 TiO3, (Ca 1 / 3 Sr1 / 3 Ba 1 / 3 ) 0.81 La 0.19 TiO3, (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.78 La 0.22 TiO3, (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.6 La 0.4 The curve of Seebeck coefficient of TiO3 changing with temperature.

[0036] Fig. 9 The present invention is a high entropy perovskite thermoelectric ceramic (CaCO3, SrCO3, BaCO3, La2O3, TiO2) made of A-site non-equimolar ratio 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.9 La 0.1 TiO3, (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.81 La 0.19 TiO3, (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.78 La 0.22 TiO3, (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.6 La 0.4 Thermoelectric ZT figure of merit of TiO3 changes with temperature. Fig.10 It is a flow chart of the present invention.

[0037] In the figure:

[0038] 1 is (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.6 La 0.4 X-ray diffraction pattern of TiO3;

[0039] 2 is (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.78 La 0.22 X-ray diffraction pattern of TiO3;

[0040] 3 is (Ca 1 / 3Sr 1 / 3 Ba 1 / 3 ) 0.81 La 0.19 X-ray diffraction pattern of TiO3;

[0041] 4 is (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.9 La 0.1 X-ray diffraction pattern of TiO3;

[0042] 5 is SrTiO3 standard PDF card #84-0444;

[0043] 6 is (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.78 La 0.22 Thermal conductivity of TiO3 versus temperature;

[0044] 7 is (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.9 La 0.1 Thermal conductivity of TiO3 versus temperature;

[0045] 8 is (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.81 La 0.19 Thermal conductivity of TiO3 versus temperature;

[0046] 9 is (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.6 La 0.4 Thermal conductivity of TiO3 versus temperature;

[0047] 10 is (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.78 La 0.22 The conductivity of TiO3 changes with temperature;

[0048] 11 is (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.81 La 0.19 The conductivity of TiO3 changes with temperature;

[0049] 12 is (Ca1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.9 La 0.1 The conductivity of TiO3 changes with temperature;

[0050] 13 is (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.6 La 0.4 The conductivity of TiO3 changes with temperature;

[0051] 14 is (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.6 La 0.4 The curve of Seebeck coefficient of TiO3 changing with temperature;

[0052] 15 is (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.78 La 0.22 The curve of Seebeck coefficient of TiO3 changing with temperature;

[0053] 16 is (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.81 La 0.19 The curve of Seebeck coefficient of TiO3 changing with temperature;

[0054] 17 is (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.9 La 0.1 The curve of Seebeck coefficient of TiO3 changing with temperature;

[0055] 18 is (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.81 La 0.19 Thermoelectric ZT figure of merit of TiO3 changes with temperature;

[0056] 19 is (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.78 La 0.22 Thermoelectric ZT figure of merit of TiO3 changes with temperature;

[0057] 20 is (Ca 1 / 3 Sr1 / 3 Ba 1 / 3 ) 0.9 La 0.1 Thermoelectric ZT figure of merit of TiO3 changes with temperature;

[0058] 21 is (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.6 La 0.4 Thermoelectric ZT figure of merit of TiO3 changes with temperature. DETAILED DESCRIPTION

[0059] The present invention is a high entropy perovskite thermoelectric ceramic with non-equimolar ratio at A site, and its actual characteristics are described in detail through four embodiments. The chemical composition of the high entropy perovskite thermoelectric ceramic with non-equimolar ratio at A site is (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.6~ 0.9 La 0.1~0.4 TiO3.

[0060] The raw materials and reagents used in each example are all commercially available products of analytical grade. Table 1 shows the chemical composition formula and raw material dosage of each example.

[0061] Table 1 Chemical composition formula and raw material dosage of each example

[0062]

[0063]

[0064] Example 1

[0065] A non-equimolar ratio high entropy perovskite thermoelectric ceramic at A site, the chemical composition of the non-equimolar ratio high entropy perovskite thermoelectric ceramic at A site is (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.9 La 0.1 TiO3.

[0066] A non-equimolar ratio high entropy perovskite thermoelectric ceramic (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.9 La 0.1 The preparation method of TiO3 comprises the following steps:

[0067] Step 1, ingredients.

[0068] According to (Ca 1 / 3 Sr 1 / 3 Ba1 / 3 ) 0.9 La 0.1 Weigh the raw materials accurately in the stoichiometric ratio of the TiO3 chemical formula.

[0069] Step 2, ball milling.

[0070] Add anhydrous ethanol and ball milling beads to the raw powder weighed in step 1, and ball mill at a speed of 250 r / min for 12 hours in a polytetrafluoroethylene ball mill. Put the ball-milled slurry into an oven, dry it at 50°C for 12 hours, and then grind it into powder with a powder particle size of 2 to 4 μm.

[0071] The mass ratio of the anhydrous ethanol to the raw material is 1:1, and the mass ratio of the ball milling beads to the raw material is 2:1.

[0072] Step 3, pre-burning.

[0073] The powder obtained in step 2 was placed in a high-temperature muffle furnace, heated to 1200°C at a heating rate of 3°C / min, and then kept at this temperature for 2 hours for pre-sintering. After the insulation was completed, the temperature was lowered to 500°C at a rate of 4°C / min; cooled to room temperature with the furnace, and (Ca 1 / 3Sr 1 / 3 Ba 1 / 3 ) 0.9 La 0.1 TiO3 high entropy ceramic powder.

[0074] Step 4, secondary ball milling.

[0075] The (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.9 La 0.1 TiO3 high entropy ceramic powder was ball milled twice, and the ball milling process was the same as step 2 to obtain (Ca) with an average particle size of 3.4 μm. 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.9 La 0.1 TiO3 high entropy ceramic powder.

[0076] Step 5: Spark plasma sintering.

[0077] The obtained powder after secondary ball milling was loaded into a graphite mold and sintered by spark plasma sintering process. The sintering environment was vacuum, and the axial pressure of the pressure head on the graphite mold was 30MPa; the temperature was raised to 1150℃ at a heating rate of 100℃ / min and then kept warm for 3min. After the insulation, the temperature was lowered to 600℃ at a rate of 100℃ / min; the furnace was cooled to room temperature, and the A-site non-equimolar high entropy perovskite dense ceramic (Ca 1 / 3 Sr1 / 3 Ba 1 / 3 ) 0.9 La 0.1 TiO3.

[0078] Step 6, reduction annealing.

[0079] Graphite powder was added to an alumina crucible. The obtained ceramic was placed in the alumina crucible; and the crucible was placed in a tube furnace. Argon was introduced into the tube furnace, and the temperature was raised to 1200°C at a rate of 2°C / min and kept at this temperature for 4 hours. The A-site non-equimolar high entropy perovskite thermoelectric ceramic (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.9 La 0.1 TiO3.

[0080] The A-site non-equimolar ratio high entropy perovskite thermoelectric ceramics (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.9 La 0.1 The phase composition of TiO3 is as follows Figure 1 The internal microstructure of the ceramic and the distribution of Ca, Sr, Ba, La, and Ti are shown in Figure 2 As shown; the curve of the change of thermal conductivity of ceramics with temperature is as follows Figure 6 As shown; the curve of ceramic conductivity changing with temperature is shown Figure 7 As shown; the curve of the ceramic Seebeck coefficient changing with temperature is shown in Figure 8 As shown; the curve of the ceramic ZT figure of merit changing with temperature is as follows Fig. 9 shown.

[0081] Example 2

[0082] A non-equimolar ratio high entropy perovskite thermoelectric ceramic at A site, the chemical composition of the non-equimolar ratio high entropy perovskite thermoelectric ceramic at A site is (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.81 La 0.19 TiO3.

[0083] A non-equimolar ratio high entropy perovskite thermoelectric ceramic (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.81 La 0.19 The preparation method of TiO3 comprises the following steps:

[0084] Step 1, ingredients.

[0085] According to (Ca1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.81 La 0.19 Weigh the raw materials accurately in the stoichiometric ratio of the TiO3 chemical formula.

[0086] Step 2, ball milling.

[0087] Add anhydrous ethanol and ball milling beads to the raw material powder weighed in step 1, and ball mill at a speed of 300 r / min for 16 hours in a polytetrafluoroethylene ball mill. Put the ball-milled slurry into an oven, dry it at 53°C for 5 hours, and then grind it into powder with a particle size of 2 to 4 μm.

[0088] The mass ratio of the anhydrous ethanol to the raw material is 1:1, and the mass ratio of the ball milling beads to the raw material is 2:1.

[0089] Step 3, pre-burning.

[0090] The powder obtained in step 2 was placed in a high-temperature muffle furnace, heated to 1150°C at a heating rate of 5°C / min for pre-sintering, and kept warm for 4 hours. After the insulation, the powder was cooled to 500°C at a rate of 2°C / min, and cooled to room temperature with the furnace to obtain (Ca 1 / 3 Sr 1 / 3Ba 1 / 3 ) 0.81 La 0.19 TiO3 high entropy ceramic powder.

[0091] Step 4, secondary ball milling.

[0092] The (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.81 La 0.19 TiO3 high entropy ceramic powder was subjected to secondary ball milling, and the ball milling process was the same as step 2 to obtain (Ca) with an average particle size of 2.7 μm. 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.81 La 0.19 TiO3 high entropy ceramic powder.

[0093] Step 5: Spark plasma sintering.

[0094] The powder obtained after secondary ball milling in step 4 is loaded into a graphite mold and sintered by spark plasma sintering technology. The sintering environment is vacuum, the axial pressure of the pressure head on the graphite mold is 35 MPa, the heating rate is 100 ° C / min, and the temperature is heated to 1200 ° C. and kept for 5 minutes, and then cooled to 600 ° C at a rate of 100 ° C / min and cooled with the furnace to obtain A-site non-equimolar high entropy perovskite dense ceramic (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.81 La 0.19 TiO3.

[0095] Step 6, reduction annealing.

[0096] The ceramic obtained in step 5 was placed in an alumina crucible with graphite powder added, and the crucible was placed in a tube furnace, argon was introduced, and the temperature was raised to 1400°C at a rate of 3°C / min and kept for 8 hours. 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.81 La 0.19 TiO3.

[0097] According to the above steps, the A-site non-equimolar ratio high entropy perovskite thermoelectric ceramic (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.81 La 0.19 TiO3 ceramics, its phase composition is as follows Figure 1 The internal microstructure of the ceramic and the distribution of Ca, Sr, Ba, La, and Ti are shown in Figure 3 As shown; the curve of the change of thermal conductivity of ceramics with temperature is as follows Figure 6 As shown; the curve of ceramic conductivity changing with temperature is shown Figure 7 As shown; the curve of the ceramic Seebeck coefficient changing with temperature is shown in Figure 8 As shown; the curve of the ceramic ZT figure of merit changing with temperature is as follows Fig. 9 shown.

[0098] Example 3

[0099] A non-equimolar ratio high entropy perovskite thermoelectric ceramic at A site, the chemical composition of the non-equimolar ratio high entropy perovskite thermoelectric ceramic at A site is (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.78 La 0.22 TiO3.

[0100] A non-equimolar ratio high entropy perovskite thermoelectric ceramic (Ca1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.78 La 0.22 The preparation method of TiO3 comprises the following steps:

[0101] Step 1, ingredients.

[0102] According to (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.78 La 0.22 Weigh the raw materials accurately in the stoichiometric ratio of the TiO3 chemical formula.

[0103] Step 2, ball milling.

[0104] Add anhydrous ethanol and ball milling beads to the raw powder weighed in step 1, and ball mill at a speed of 350 r / min for 20 hours in a polytetrafluoroethylene ball mill. Put the ball-milled slurry into an oven, dry it at 56°C for 3 hours, and then grind it into powder with a powder particle size of 2 to 4 μm.

[0105] The mass ratio of the anhydrous ethanol to the raw material is 1:1, and the mass ratio of the ball milling beads to the raw material is 2:1.

[0106] Step 3, pre-burning.

[0107] The powder obtained in step 2 was placed in a high-temperature muffle furnace, heated to 1200°C at a heating rate of 5°C / min for pre-sintering, and kept warm for 4 hours. After the insulation, the powder was cooled to 500°C at a rate of 4°C / min, and cooled to room temperature with the furnace to obtain (Ca 1 / 3 Sr 1 / 3Ba 1 / 3 ) 0.78 La 0.22 TiO3 high entropy ceramic powder.

[0108] Step 4, secondary ball milling.

[0109] The (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.78 La 0.22 TiO3 high entropy ceramic powder was subjected to secondary ball milling, and the ball milling process was the same as step 2 to obtain (Ca) with an average particle size of 3.1 μm. 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.78 La 0.22 TiO3 high entropy ceramic powder.

[0110] Step 5: Spark plasma sintering.

[0111] The powder obtained after secondary ball milling in step 4 is loaded into a graphite mold and sintered by spark plasma sintering technology. The sintering environment is vacuum, the axial pressure of the pressure head on the graphite mold is 40MPa, the heating rate is 100℃ / min, and the temperature is kept at 1250℃ for 3min, then cooled to 600℃ at a rate of 100℃ / min and cooled with the furnace to obtain A-site non-equimolar high entropy perovskite dense ceramic (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.78 La 0.22 TiO3.

[0112] Step 6, reduction annealing.

[0113] The ceramic obtained in step 5 was placed in an alumina crucible with graphite powder added, and the crucible was placed in a tube furnace, argon was introduced, and the temperature was raised to 1300°C at a rate of 4°C / min and kept for 6 hours. 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.78 La 0.22 TiO3.

[0114] According to the above steps, the A-site non-equimolar ratio high entropy perovskite thermoelectric ceramic (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.78 La 0.22 TiO3 ceramics, its phase composition is as follows Figure 1 The internal microstructure of the ceramic and the distribution of Ca, Sr, Ba, La, and Ti are shown in Figure 4 As shown; the curve of the change of thermal conductivity of ceramics with temperature is as follows Figure 6 As shown; the curve of ceramic conductivity changing with temperature is shown Figure 7 As shown; the curve of the ceramic Seebeck coefficient changing with temperature is shown in Figure 8 As shown; the curve of the ceramic ZT figure of merit changing with temperature is as follows Fig. 9 shown.

[0115] Example 4

[0116] A non-equimolar ratio high entropy perovskite thermoelectric ceramic at A site, the chemical composition of the non-equimolar ratio high entropy perovskite thermoelectric ceramic at A site is (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.6 La 0.4 TiO3.

[0117] A non-equimolar ratio high entropy perovskite thermoelectric ceramic (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.6 La 0.4 The preparation method of TiO3 comprises the following steps:

[0118] Step 1, ingredients.

[0119] According to (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.6 La 0.4 Weigh the raw materials accurately in the stoichiometric ratio of the TiO3 chemical formula.

[0120] Step 2, ball milling.

[0121] Add anhydrous ethanol and ball milling beads to the raw material powder weighed in step 1, and ball mill at a speed of 320 r / min for 24 hours in a polytetrafluoroethylene ball mill. Put the ball-milled slurry into an oven, dry it at 60°C for 7 hours, and then grind it into powder with a powder particle size of 2 to 4 μm.

[0122] The mass ratio of the anhydrous ethanol to the raw material is 1:1, and the mass ratio of the ball milling beads to the raw material is 2:1.

[0123] Step 3, pre-burning.

[0124] The powder obtained in step 2 was placed in a high-temperature muffle furnace, heated to 1250°C at a heating rate of 3°C / min for pre-sintering, and kept warm for 4 hours. After the insulation, the powder was cooled to 500°C at a rate of 3°C / min, and cooled to room temperature with the furnace to obtain (Ca 1 / 3 Sr 1 / 3Ba 1 / 3 ) 0.6 La 0.4 TiO3 high entropy ceramic powder.

[0125] Step 4, secondary ball milling.

[0126] The (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.6 La 0.4 TiO3 high entropy ceramic powder was ball milled twice, and the ball milling process was the same as step 2 to obtain (Ca) with an average particle size of 3.4 μm. 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.6 La 0.4 TiO3 high entropy ceramic powder.

[0127] Step 5: Spark plasma sintering.

[0128] The powder obtained after secondary ball milling in step 4 is loaded into a graphite mold and sintered by spark plasma sintering technology. The sintering environment is vacuum, the axial pressure of the pressure head on the graphite mold is 30 MPa, the heating rate is 100 ° C / min, and the temperature is heated to 1250 ° C for 7 minutes, and then the temperature is reduced to 600 ° C at a rate of 100 ° C / min and then cooled in the furnace to obtain A-site non-equimolar high entropy perovskite dense ceramic (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.6 La 0.4 TiO3.

[0129] Step 6, reduction annealing.

[0130] The ceramic obtained in step 5 was placed in an alumina crucible with graphite powder added, and the crucible was placed in a tube furnace, argon was introduced, and the temperature was raised to 1400°C at a rate of 5°C / min and kept for 8 hours. 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.6 La 0.4 TiO3.

[0131] Table 2 Chemical composition of each example

[0132]

[0133] Table 3 Process parameters for each implementation

[0134]

[0135]

[0136] Table 4 (Ca) obtained in each embodiment 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.6 La 0.4 Average particle size of TiO3 high entropy ceramic powder

[0137]

[0138]

[0139] According to the above steps, the A-site non-equimolar ratio high entropy perovskite thermoelectric ceramic (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 0.6 La 0.4TiO3, its phase composition is as follows Figure 1 The internal microstructure of the ceramic and the distribution of Ca, Sr, Ba, La, and Ti are shown in Figure 5 As shown; the curve of the change of thermal conductivity of ceramics with temperature is as follows Figure 6 As shown; the curve of ceramic conductivity changing with temperature is shown Figure 7 As shown; the curve of the ceramic Seebeck coefficient changing with temperature is shown in Figure 8 As shown; the curve of the ceramic ZT figure of merit changing with temperature is as follows Fig. 9 shown.

[0140] Determination of the phase structure of non-equimolar ratio A-site high entropy perovskite structure ceramics:

[0141] X-ray diffraction (XRD) was used to analyze the phase of the A-site non-equimolar ratio high entropy perovskite thermoelectric ceramics. The instrument used was an X'Pert PRO diffractometer from the Netherlands Analytical Instruments Company. The scanning angle range was: 2θ = 10-90°, the scanning speed was 5° / min, and the step length was 0.01°. The powder diffraction results were as follows: Figure 1 .

[0142] Determination of the microstructure and element distribution of non-equimolar high-entropy perovskite thermoelectric ceramics at the A site:

[0143] The microscopic morphology of the cross section of the A-site non-equimolar ratio high entropy perovskite thermoelectric ceramic sample was observed using a focused ion / electron dual beam electron microscope (FIB: Helios G4 CX) from FEI, USA. The distribution of various elements that may exist in the area observed by the electron microscope was tested using an energy dispersive spectrometer (EDS: Thermo NS7) from Thermofisher. Figure 2-5 As shown. Figure 2-5 It can be seen that the A-site non-equimolar ratio high-entropy perovskite thermoelectric ceramics of the present invention have complete grains and the elements Ca, Sr, Ba, La, and Ti are evenly distributed.

[0144] Determination of thermal conductivity of non-equimolar ratio A-site high entropy perovskite structure ceramics:

[0145] The LFA-427 laser thermal conductivity tester from Netzsch, Germany, was used to directly test the thermal diffusion coefficient α of the A-site non-equimolar high entropy perovskite thermoelectric ceramics. p The size of the sample is Φ12.7mm×lmm. According to the thermal conductivity calculation formula κ=α×C p ×ρ to obtain the thermal conductivity of the sample.

[0146] Determination of electrical conductivity and Seebeck coefficient of A-site non-equimolar high entropy perovskite thermoelectric ceramics:

[0147] Wuhan Jiayitong's thermoelectric parameter testing system (Namicro-03) was used to simultaneously test the conductivity and Seebeck coefficient of the A-site non-equimolar ratio high-entropy perovskite thermoelectric ceramics. The test temperature range was from room temperature to 1073K, the heating rate was 10K / min, and the test environment was vacuum.

[0148] A-site non-equimolar high entropy perovskite thermoelectric ceramics (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 1-x La x The thermoelectric properties of TiO3 at 1073K are listed in Table 3.

[0149] Table 3. Thermoelectric properties of A-site non-equimolar high entropy perovskite thermoelectric ceramics at 1073K

[0150]

Claims

1. A non-equimolar high entropy thermoelectric ceramic, characterized in that: The chemical formula of non-equimolar high entropy perovskite ceramic thermoelectric ceramic is (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 1-x La x TiO3, (x=0.1~0.4).

2. The non-equimolar ratio high entropy thermoelectric ceramic according to claim 1, characterized in that: The synthesis of (Ca 1 / 3 Sr 1 / 3Ba 1 / 3 ) 1-x La x The raw materials of TiO3 are CaCO3, SrCO3, BaCO3, La2O3 and TiO2. The particle sizes are all micron-level and the purity is analytical grade.

3. A method for preparing the non-equimolar ratio high entropy thermoelectric ceramic according to claim 1, characterized in that: The specific process is: Step 1, Ingredients: Weigh each initial raw material according to the stoichiometric ratio of each component in the chemical composition formula of the high entropy perovskite ceramic; Step 2, preparing powder: The weighed raw material powder is ball-milled with anhydrous ethanol as a ball-milling medium and zirconium oxide balls as ball-milling beads to obtain a slurry; the slurry is dried and ground to obtain a powder; Step 3, pre-burning: The obtained powder was placed in a sealed crucible and calcined in a high-temperature muffle furnace to obtain (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 1-x La x TiO3 high entropy ceramic powder; Step 4, secondary ball milling: The obtained (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 1-x La x The TiO3 high entropy ceramic powder is subjected to secondary ball milling, and the ball milling process is the same as the ball milling process for preparing the powder in step 2; a high entropy ceramic powder with an average particle size of 2.7 to 3.4 μm is obtained; Step 5, Spark Plasma Sintering: After the second ball milling, (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 1-x La x TiO3 high entropy ceramic powder is loaded into a graphite mold and sintered by spark plasma sintering process to obtain A-site non-equimolar high entropy perovskite dense ceramic; Step 6, reduction annealing: The obtained ceramic is placed in an alumina crucible with graphite powder added, and the crucible is placed in a tube furnace, argon gas is introduced, and annealing is performed; the A-site non-equimolar ratio high entropy perovskite thermoelectric ceramic (Ca 1 / 3 Sr 1 / 3 Ba 1 / 3 ) 1-x La x TiO3.

4. The method for preparing the non-equimolar ratio high entropy thermoelectric ceramic according to claim 1, characterized in that: When preparing the powder, the weight ratio of the ball milling medium to the raw material powder is 1:1, and the weight ratio of the ball milling beads to the raw material powder is 2:

1.

5. The method for preparing the non-equimolar ratio high entropy thermoelectric ceramic according to claim 1, characterized in that: When preparing the powder, the ball mill speed is 250-350 r / min, the ball milling time is 12-24 h; the drying temperature is 50-60° C., and the drying time is 3-12 h.

6. The method for preparing the non-equimolar ratio high entropy thermoelectric ceramic according to claim 1, characterized in that: During the pre-firing, the heating rate is 2-5°C, the pre-firing temperature is 1150-1250°C, the heat preservation time is 2-4h, the cooling rate is 2-5°C, and the cooling temperature is 500°C.

7. The method for preparing the non-equimolar ratio high entropy thermoelectric ceramic according to claim 1, characterized in that: During the spark plasma sintering, the sintering environment is vacuum, the axial pressure of the pressure head on the graphite mold is 30-40MPa, the heating rate is 100°C / min, and the temperature is kept at 1150-1250°C for 3-7min; the temperature is reduced to 600°C at a rate of 100°C / min and then cooled with the furnace.

8. The method for preparing the non-equimolar ratio high entropy thermoelectric ceramic according to claim 1, characterized in that: During the reduction annealing, the annealing temperature is 1200-1400° C., the heating rate of the tubular furnace is 2-5° C. / min, and the insulation time is 4-8 hours.

Citation Information

Patent Citations

  • High-entropy oxides for thermal barrier coating (TBC) top coats

    CA3106049A1

  • A-site high-entropy perovskite oxide and preparation method thereof

    CN109650876A

  • B-site high-entropy perovskite oxide Sr0.9La0.1MO3 ceramic and preparation method thereof

    CN112897989A

  • A-site high-entropy perovskite oxide MeTiO3 thermoelectric ceramic and preparation method thereof

    CN112960978A

  • High-energy-storage non-equimolar-ratio high-entropy perovskite oxide ceramic material and preparation method thereof

    CN114085079A

Cited By

  • Perovskite type high-temperature thermoelectric ceramic material and preparation method thereof

    CN120040183A

  • Perovskite high-temperature thermoelectric ceramic material and preparation method thereof

    CN120040183B

  • AlTiO3-based high-entropy ceramic as well as preparation method and application thereof

    CN120329030A